2019
DOI: 10.21203/rs.2.13853/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge of HIV post exposure prophylaxis among public healthcare providers in Ilala District, Dar es Salaam

Abstract: Background Post-exposure prophylaxis (PEP) using highly active antiretroviral therapy (HAART) significantly reduces the risk of HIV infection to the victims. Evidence based practice has brought dynamicity in HAART regimens necessitating continual updates on knowledge of health care providers (HCPs) regarding PEP. Therefore, this study aimed to assess contemporary knowledge of HCPs on PEP three years after the introduction of Tenofovir based HAART regimens as a default for PEP in Tanzania.Methods A health care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…In this study, the availability of HIV PEP guidelines had no association with the level of knowledge among HCWs, which is similar to a study performed in Nigeria that revealed unacceptable disconnects between doctors and the existence of durable PEP guideline policies in hospitals [18]. Contrary to a study conducted in Dar Es Salaam, Tanzania, where the majority of respondents acquired knowledge on HIV PEP from HIV treatment guidelines [12]., other studies prevail in the strong association between guidelines and knowledge on HIV PEP [17]. This could be because in the current study, there was reluctance to emphasize the dissemination use of upadated HIV PEP guidelines compared to previous studies when PEP guidelines were implemented.…”
Section: Association Between Work-related Factors and Knowledge Of Hi...supporting
confidence: 79%
See 1 more Smart Citation
“…In this study, the availability of HIV PEP guidelines had no association with the level of knowledge among HCWs, which is similar to a study performed in Nigeria that revealed unacceptable disconnects between doctors and the existence of durable PEP guideline policies in hospitals [18]. Contrary to a study conducted in Dar Es Salaam, Tanzania, where the majority of respondents acquired knowledge on HIV PEP from HIV treatment guidelines [12]., other studies prevail in the strong association between guidelines and knowledge on HIV PEP [17]. This could be because in the current study, there was reluctance to emphasize the dissemination use of upadated HIV PEP guidelines compared to previous studies when PEP guidelines were implemented.…”
Section: Association Between Work-related Factors and Knowledge Of Hi...supporting
confidence: 79%
“…Kasulu district hospital was associated with adequate knowledge compared to Kibondo district hospital and Kigoma regional hospital either due to available PEP service and guidelines that have an in uence on the association of knowledge as well as the presence of strong management and leadership practices that strengthen the health system together with other health partners who collaborate to in uence principles for improving quality management in healthcare. The association between facilities in which HCWs work with adequate knowledge is contrary to a study performed in Dar Es Salaam, Tanzania, which reported on sociodemographic factors such as level of education in association with inadequate knowledge of which certi cate level of education appeared to have low knowledge of HIV PEP [12]. Another study reported in Dar Es Salaam, Tanzania that a low level of PEP knowledge was especially among lower carder means medical attendants [4].…”
Section: Association Between Sociodemographic Factors and Knowledge O...mentioning
confidence: 68%